Could Pictorial Health Warning Change Smoking Behavior among Teenagers? : A Cross-Sectional Study among Junior High School Students - Ranti Yunita Hidayah; Novia Handayani; Syamsulhuda B Musthofa (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2019)
Abstract Background: The Indonesian Ministry of Health has established a regulation about the inclusion of pictorial health warning and information on the packages of tobacco product since 2013. It was intended to encourage smokers to stop smoking. This study aimed to analyze the effect of pictorial health warning to teenagers’ smoking behavior.Methods: This was a quantitative study with cross sectional research design. The population was junior high school students in Semarang City. The samples were chosen from 16 junior high schools in Semarang City, representing 16 districts. Each junior high school was chosen by using probability sampling techniques. A total of 160 respondents were chosen by using simple random sampling method.Results: The results showed that variables which have relationship with smoking behavior among teenagers were accessibility (p = 0.006), exposure (p = 0.039) and peer support (p = 0.008). Variables which did not have relationship with smoking behavior among teenagers were pocket money (p = 0.112), daily cigarette use (p = 0.641), knowledge (p = 0.535), attitude (p = 0.759)Conclusion: The inclusion of pictorial health warning, especially on the packages of tobacco product encourage students as novice smokers to stop smoking.